A common process of bioaccumulation of rare earth elements, iron, and aluminium in three Tetrahymena species - Jana Kohl-Chandramohan; Michael Schweikert; Tobias Junginger; Ingo Hartenbach; Marie-Louise Lemloh (Ecotoxicology and Environmental Safety)
Understanding how organisms interact with elements used in technical applications is essential because of the increasing prevalence of these elements in the environment. The unicellular eukaryote ciliate Tetrahymena can tolerate high concentrations of cytotoxic metals and is known to have developed several detoxification strategies, in particular the intracellular bioaccumulation. In this study, we systematically investigated the process of tolerance and intracellular bioaccumulation of several metals (La, Ce, Sm, Eu, Gd, Dy, Fe, and Al) in three species of the ciliate Tetrahymena (T. pyriformis, T. thermophila, and T. pigmentosa). In all three species and for all tested elements, treatment of the cells with dissolved metals in an organic growth medium leads to an intracellular bioaccumulation and formation of biogenic metal-containing particles within the food vacuoles of the cells. Stable particles are excreted into the surrounding medium within 2 h. The particles have a species-dependent diameter between 2.4 and 3.2 µm and consist of the respective added metal La, Ce, Sm, Eu, Gd, Dy, Fe, or Al together with the elements C, O, P, Na, Mg, K, and Ca. Intracellular bioaccumulation is associated with a 26–87 % depletion of the rare earth element concentrations in the medium within 48 h. The understanding of microbial bioaccumulation pathways is a promising approach for the development of new bio-inspired strategies for recycling or remediation applications.